(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the theoretical essence of the concept of professional pedagogical erudition, its structural components, and its integrative and pedagogical significance in the development of students’ professional training. It also substantiates the effective conditions for the formation of pedagogical erudition.